2015
DOI: 10.1038/srep08078
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Signal-regulating Kinase 1 promotes Ochratoxin A-induced renal cytotoxicity

Abstract: Oxidative stress and apoptosis are involved in Ochratoxin A (OTA)-induced renal cytotoxicity. Apoptosis signal-regulating kinase 1 (ASK1) is a Mitogen-Activated Protein Kinase Kinase Kinase (MAPKKK, MAP3K) family member that plays an important role in oxidative stress-induced cell apoptosis. In this study, we performed RNA interference of ASK1 in HEK293 cells and employed an iTRAQ-based quantitative proteomics approach to globally investigate the regulatory mechanism of ASK1 in OTA-induced renal cytotoxicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…Oxidative stress is often cited as a key mechanism in OTA-induced apoptosis in different cell types (Marin-Kuan et al, 2011): it has been reported that OTA accelerates reactive oxygen species (ROS) formation by lipid peroxidation and the inhibition of antioxidant enzymes such as superoxide dismutase. Increased ROS induce Ca 2+ release from intracellular organelles, affecting MAPK phosphorylation and the intracellular signaling cascade (Liang et al, 2015). In vitro OTA stimulated the phosphorylation of three major MAPKs identified in mammalian cells: ERK1/2, JNK and p38.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is often cited as a key mechanism in OTA-induced apoptosis in different cell types (Marin-Kuan et al, 2011): it has been reported that OTA accelerates reactive oxygen species (ROS) formation by lipid peroxidation and the inhibition of antioxidant enzymes such as superoxide dismutase. Increased ROS induce Ca 2+ release from intracellular organelles, affecting MAPK phosphorylation and the intracellular signaling cascade (Liang et al, 2015). In vitro OTA stimulated the phosphorylation of three major MAPKs identified in mammalian cells: ERK1/2, JNK and p38.…”
Section: Discussionmentioning
confidence: 99%
“…15 In brief, the cells were treated as above and then washed once with PBS and incubated with JC-1 (Beyotime, China) staining solution (5 mg/ml) for 20 min at 37 C. After the cells were washed twice with the JC-1 staining buffer, the fluorescence densities of the JC-1 monomers ( ex ¼ 488 nm, em ¼ 529 nm) and JC-1 aggregates ( ex ¼ 524 nm, em ¼ 594 nm) were detected using a microplate reader. The Á m of the HEK293 and HepG2 cells was expressed as the fluorescence intensity ratio of the JC-1 aggregates over the JC-1 monomers.…”
Section: á M Assaymentioning
confidence: 99%
“…After 1μM OTA treatment for 5 h, the biological processes that the changed proteins were involved in included metabolic process, cellular process, cellular component organization, developmental process, cell communication, immune system process, generation of precursor metabolites and energy, transport, system process, response to stimulus, cell cycle and cell adhesion. In Liang et al’ s study, 20 μM OTA exposure for 24 h to apoptosis signal‐regulating kinase 1 knockdown HEK 293 cells exerted influences on mRNA splicing, nucleotide metabolism, the cell cycle, DNA repair, and lipid and lipoprotein metabolism . Different exposure time and OTA concentration may contribute to the different enriched pathways.…”
Section: Resultsmentioning
confidence: 99%